2003
DOI: 10.1242/dev.00503
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ablation of CCAP neuropeptide-containing neurons ofDrosophilacauses specific defects in execution and circadian timing of ecdysis behavior

Abstract: Insect growth and metamorphosis is punctuated by molts, during which a new cuticle is produced. Every molt culminates in ecdysis, the shedding of the remains of the old cuticle. Both the timing of ecdysis relative to the molt and the actual execution of this vital insect behavior are under peptidergic neuronal control. Based on studies in the moth, Manduca sexta, it has been postulated that the neuropeptide Crustacean cardioactive peptide (CCAP)plays a key role in the initiation of the ecdysis motor program. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
281
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(302 citation statements)
references
References 49 publications
21
281
0
Order By: Relevance
“…Kir2.1 thus appears to be a more effective suppressor of N CCAP function than reaper, which had a pupal mortality rate of 79% (283 of 357 animals) in parallel crosses. The survival of adults expressing reaper likely results from incomplete killing of N CCAP neurons in some animals, as reported previously by Park et al (2003). However, we observed no loss of N CCAP neurons in pharate adults expressing 3ϫ EKO (Fig.…”
Section: Suppression Of Excitability In N Ccap Inhibits Wing Expansiosupporting
confidence: 88%
See 2 more Smart Citations
“…Kir2.1 thus appears to be a more effective suppressor of N CCAP function than reaper, which had a pupal mortality rate of 79% (283 of 357 animals) in parallel crosses. The survival of adults expressing reaper likely results from incomplete killing of N CCAP neurons in some animals, as reported previously by Park et al (2003). However, we observed no loss of N CCAP neurons in pharate adults expressing 3ϫ EKO (Fig.…”
Section: Suppression Of Excitability In N Ccap Inhibits Wing Expansiosupporting
confidence: 88%
“…The temperature sensitivity of Shi ts1 allows dynamin function to be acutely inhibited by shifting flies to the restricted temperature. Park et al (2003) have reported previously that expression of UAS-Shi ts1 within N CCAP yields flies with the juvenile phenotype. However, because suppression of dynamin function in these experiments was constitutive rather than acute, with flies raised at the restricted temperature, the observed phenotypes may have derived from pleiotropic developmental defects distinct from suppression of synaptic transmission (Kitamoto, 2001).…”
Section: Enhancement Of Excitability Of N Ccap Also Inhibits Wing Expmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pathways participate in wing expansion; a neuroendocrine cascade (McNabb et al, 1997;Park et al, 2003;Dewey et al, 2004;Luan et al, 2006) and tissue remodeling of the wing itself (Kiger et al, 2007). Given the neural localization of unf transcripts, the three sets of peptidergic neurons that comprise the neuroendocrine cascade that regulates wing expansion behaviors are candidates that may be responsible for the wing expansion defects of unf mutants.…”
Section: Discussionmentioning
confidence: 99%
“…We expressed mRFPHttQ138 using CCAP-GAL4 that expresses in a single neuron per hemisegment (Park et al 2003;Vomel and Wegener 2007). This driver allows single-cell resolution for assaying how soluble HttQ138 interacts with larger aggregates.…”
Section: Kinetics Of Httq138 Aggregate Formationmentioning
confidence: 99%